Mineralogical distribution of base metal sulfides in processing products of black shale-hosted Kupferschiefer-type ore. (April 2018) - Kamradt, A.; Walther, S.; Schaefer, J.; Hedrich, S.; Schippers, A.
Highlights: Mineralogical distribution of sulfides and gangue by automated particle analysis. Black shale ore dressed by improved flotation combined with bioleaching. Copper concentrate efficiently bioleached, but incomplete chalcopyrite dissolution. Detailed imaging of particles featuring intergrowth and dissolution textures. Potentially applicable for the exploitation of complex organic-rich ore deposits. Abstract: The extraction of copper from black shales associated with fine-grained and complex base metal ore mineralization traditionally using pyrometallurgy becomes increasingly uneconomic, because one of the most significant cost factors is the high energy consumption. Thus, energy-saving alternative mineral processing methods are to be considered to improve the metal recovery route economically and environmentally. In this study, a milled, organic carbon-rich black shale ore from the Sangerhausen mining district in central Germany has been pre-treated by ethanol prior to the froth flotation tests to gain a copper concentrate marked by an increased copper content and more efficient copper recovery. The flotation product (15.3% Cu) was used for biohydrometallurgically batch tests to extract copper and associated trace metals. SEM-based automated particle analyses on the comminuted black shale ore, flotation product as well as tailings, bioleaching residues and abiotic leaching residues were used to trace the recovery performance particularly of copper sulfides. The black shale ore is characterized by high contents of bornite (2.8 wt%) and chalcopyrite (1.3 wt%) associated with a high grade of pyrite (5.8 wt%). Considerable enrichments were achieved in the flotation product for bornite (20.7 wt%) and chalcopyrite (10.3 wt%) as well as for galena and sphalerite, while pyrite was successfully depressed in the tailings. Compared to abiotic chemical leaching, the bioleaching test of the bornite- and chalcopyrite-rich copper concentrate was particular efficient in the recovery of bornite and chalcocite. However, chalcopyrite was leached insufficiently in both, abiotic and microbial leaching tests, and presents a common component in the residues.